USING OAS.WEB.ID TO CREATE ENGLISH VOCABULARY SIZE QUIZ - Winardi, Yonathan; Hananto, Hananto (Polyglot, 2023)
ABSTRACTA systematic and continuous vocabulary assessment is required to monitor the progress of learners’ learning and readiness to follow certain instr8uctional programs. The purpose of this study is to report a tryout of constructing an online quiz using http://oas.web.id/.  OAS is an ongoing R&D project to help teachers and/or educational researchers create an online quiz by converting multiple-choice questions from a spreadsheet program (i.e. MS Excel or Google Sheets) into a Google Forms quiz, Moodle, paper-based quiz, Kahoot, or any other quiz makers that have import facility. This paper focuses on describing the making and tryout of a vocabulary-size quiz into Google Forms quiz to find out whether the resulting quiz works. The result shows that OAS offered an easy and very quick way in creating a vocabulary-size quiz successfully by copying the already available vocabulary-size questions based on Nation and Beglar’s Vocabulary Size Test. The researcher and the voluntary test students got the scores immediately after they had submitted the Google Forms. It can then be concluded that the OAS created the vocabulary quiz successfully without any serious technical problems.BAHASA INDONESIA ABSTRAKSebuah asesmen kosakata yang sistematis dan berkelanjutan diperlukan untuk memonitor kemajuan dan kesiapan pembelajar untuk mengikuti program-program pembelajaran. Tujuan dari penelitian ini adalah untuk melaporkan sebuah uji coba dari penyusunan sebuah kuis dalam jaringan menggunakan http://oas.web.id/.  OAS adalah sebuah proyek penelitian dan pengembangan untuk menolong guru-guru dan/atau peneliti-peneliti pendidikan membuat sebuah kuis dalam jaringan dengan cara mengonversi pertanyaan-pertanyaan pilihan berganda dari sebuah program lembar kerja (misalnya Microsoft Excel atau Google Sheets) ke dalam kuis Google Forms, Moodle, lembar kuis cetak, Kahoot, atau program-program pembuat kuis lainnya yang memiliki fitur impor. Paper ini fokus pada penggambaran proses pembuatan dan uji coba sebuah kuis kosakata dengan Google Forms untuk mengetahui apakah kuis tersebut bisa digunakan. Hasilnya menunjukkan bahwa OAS menawarkan sebuah cara yang mudah dan sangat cepat dalam membuat sebuah kuis kosakata dengan menyalin pertanyaan-pertanyaan kosakata yang telah disediakan berdasarkan tes kosakata Nation and Beglar’s. Peneliti dan mahasiswa/i yang berpartisipasi di uji coba, langsung mendapatkan hasil kuis setelah mereka mengumpulkan Google Forms. Kemudian dapat disimpulkan bahwa OAS sukses membuat kuis kosakata tanpa ada masalah-masalah teknis yang berarti.